Stage 3A environmental compliance of the 6-cylinder tractor engine - Kukharonak, H.; Petruchenko, A.; Predko, A.; Telyuk, D.; Кухаренок, Георгій Михайлович; Петрученко, Олександр Миколайович; Предко, Андрій Володимирович; Телюк, Дмитро Олександрович (Харківський національний автомобільно-дорожній університет, 2021)
Problem. The development strategy of the Minsk Motor Plant, implemented within the framework of plant and state scientific and technical programs, is aimed at producing competitive products that meet modern technical requirements of international standards and quality. The mandatory requirement for the successful promotion of diesel engines on the off-road vehicle market is to ensure the required environmental performance, with low fuel consumption and low engine cost. The well-known technical solutions aimed to achieve environmental indicators of the Stage 3A level significantly increase the cost of diesel engines, therefore, the achievement of the required environmental standards without a significant increase in the cost of engines can be considered an urgent task. Purpose. Stage3A Environmental Compliance for 6 Cylinder Tractor Diesel. Methodology. Experimental studies were carried out for diesel engines equipped with: a Common Rail BOSCH accumulator fuel supply system with an injection pressure of 140 MPa, injectors with 7 nozzle holes; a direct-action fuel supply system with a MOTORPAL fuel pump providing a maximum injection pressure of 100 MPa, MOTORPAL injectors and AZPI with five nozzle holes; combustion chambers of two types with bowl diameters of 55 and 67.5 mm; cylinder heads providing swirl ratios 3–4 and 3.5–4.5; high pressure exhaust gas recirculation system. The tests were carried out at characteristic points of the NRSC cycle at three crankshaft speeds: minimum idle speed 800 min-1, maximum torque 1600 min-1, and maximum power 2100 min-1. Results. It turned out that it is possible to achieve Stage3A emissions standards on 116 kW diesel engines using direct fuel equipment and a semi-open combustion chamber, on 156 kW diesel engines using a Low Cost Common Rail fuel supply system and an open combustion chamber. Originality. The results of the combustion chamber shape choice, the parameters of the fuel-injection equipment, the swirl ratio of the inlet channels, valve timings and parameters of the exhaust gas recirculation system made it possible to organize diesel engine workflow of the Stage 3A ecological level. Practical significance. Construction elements of the six-cylinder diesel engines have been developed and introduced at the Minsk Motor Plant.
Забезпечення екологічних норм Stage3A шестициліндровим тракторним дизелем
Keywords: diesel; swirl ratio; combustion chamber; fuel supply system; injector nozzle; дизель; вихрове відношення; камера згоряння; система подачі палива; розпилювач палива; 621.436.068.4; 10.30977/BUL.2219-5548.2021.94.0.188